GREEN ECONOMY, ECO-TOURISM, AND DIGITAL NOMAD ECONOMY: NEW OPPORTUNITIES FOR UZBEKISTAN - Baxromova Indira Azizjon qizi; G‘ulomova Gulasal Azizjonovna; Axmedov O‘tkirjon Aloviddin o‘g‘li (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article explores the interconnection between green economy, eco-tourism, and the digital nomad economy, and their impact on Uzbekistan's economic development. Green economy, as a sustainable economic model, offers new opportunities in the tourism sector by promoting ecological sustainability and reducing environmental impacts. Eco-tourism, by focusing on preserving natural resources, contributes to the development of sustainable tourism, while the digital nomad economy leverages remote work and digital technologies. The article examines how these trends can benefit Uzbekistan economically, create new job opportunities, and enhance sustainable development. The integration of green economy and digital nomads in Uzbekistan can provide pathways for economic growth, global integration, and environmental sustainability.